2010
DOI: 10.1007/s10494-010-9313-0
|View full text |Cite
|
Sign up to set email alerts
|

The Mesoscopic Eulerian Approach for Evaporating Droplets Interacting with Turbulent Flows

Abstract: This paper presents a statistical approach, known as mesoscopic Eulerian formalism (Février et al., J Fluid Mech 533:1-46, 2005), which is extended in order to model a cloud of inertial evaporating droplets interacting with a turbulent carrier flow. This approach is checked in a non-isothermal droplet-laden turbulent planar jet by means of a priori tests. The "measurement" of the mesoscopic particlevelocity and particle-temperature moments is accomplished by using the Eulerian particle fields computed from a D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…In the current study the droplet volume fraction is chosen to fluctuate around 10 À4 and therefore we consider twoway coupling according to the classification proposed by Elghobashi (1994). In the Lagrangian method for the droplets adopted here a system of ordinary differential equations for each droplet is obtained following the model used in Miller and Bellan (1998) and Masi et al (2010). The location of a droplet is governed by the kinematic condition:…”
Section: The Dispersed Phasementioning
confidence: 99%
See 1 more Smart Citation
“…In the current study the droplet volume fraction is chosen to fluctuate around 10 À4 and therefore we consider twoway coupling according to the classification proposed by Elghobashi (1994). In the Lagrangian method for the droplets adopted here a system of ordinary differential equations for each droplet is obtained following the model used in Miller and Bellan (1998) and Masi et al (2010). The location of a droplet is governed by the kinematic condition:…”
Section: The Dispersed Phasementioning
confidence: 99%
“…A study of the mixing layer with embedded evaporating droplets was done by Miller and Bellan (1998). In Masi et al (2010) investigated the interaction of a non-isothermal dropletladen turbulent planar jet with a cloud of inertial evaporating droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a study dedicated to the mixing layer with embedded evaporating droplets was conducted by Miller and Bellan (1998). In Masi et al (2010) a cloud of inertial evaporating droplets, interacting with a non-isothermal droplet-laden turbulent planar jet, is considered. In the present paper we extend the work of Mashayek (1998) to wall-bounded turbulence by investigating turbulent channel flow with a dispersed droplet phase undergoing phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…To enable comparison between a strictly incompressible and a more general compressible formulation, we focus the attention on a case of initially 100% relative humidity in the channel. The models adopted here are identical to the models used in Miller and Bellan (1998) and Masi et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…A study of the mixing layer with embedded evaporating droplets was reported by Miller and Bellan [2]. In 2010 Masi et al [3] investigated the interaction of a non-isothermal dropletladen turbulent planar jet with a cloud of inertial evaporating droplets. In this study we focus on wall-bounded turbulence by considering turbulent channel flow with a dispersed droplet phase undergoing phase transition.…”
Section: Introductionmentioning
confidence: 99%